Mid-term follow-up outcomes for medial patellofemoral ligament reconstruction after acute first-time patellar dislocation using nonresorbable suture tape: a case series - Zimmermann, Felix; Schickling, Lasse; Recum, Jan von; Franke, Jochen; Grützner, Paul Alfred; Vetter, Sven Y. (Orthopaedic journal of sports medicine, 2025)
Background: Reconstruction of the medial patellofemoral ligament (MPFL) with nonresorbable suture tape (FiberTape) could be an alternative to MPFL reconstruction (MPFLR) using an autologous tendon graft after a first-time patellar dislocation. - Purpose: To investigate whether good clinical and radiological results are achievable with this technique. - Level of Evidence: Case series; Level of evidence, 4. - Methods: Between January 2017 and September 2020, a total of 30 patients with acute first-time patellar dislocation and a low anatomic risk factor constellation of patellar instability underwent MPFLR using nonresorbable suture tape combined with cartilage surgery if necessary. After a minimum 2-year follow-up, the Banff Patella Instability Instrument 2.0 (BPII 2.0)—a numerical analog scale (NAS, 0-10) for patellofemoral pain (PFP) (NAS pain) and subjective knee joint function (NAS function)—was used to assess patients’ reported quality of life after surgery in 20 patients (men/women: 14/6; age, 22.2 ± 6.1 years; 67% follow-up rate). Magnetic resonance imaging (MRI) scans of the surgically treated knee joint were conducted, and the Area Measurement And DEpth & Underlying Structures (AMADEUS) scores were evaluated pre- and postoperatively. - Results: The BPII 2.0 score was 81 ± 12.5 (55.2-94.7) points postoperatively. The subjective rating of knee joint function (NAS function) was 8.5 ± 1.5 (4-10), and the PFP (NAS pain) was 1.5 ± 1.7 (0-5) postoperatively. MRI evaluations showed an increase in the AMADEUS score in all patients from 79 ± 24.3 points (40-100 points) preoperatively to 92.3 ± 9 points (75-100 points) postoperatively (P = .02). - Conclusion: MPFLR with nonresorbable suture material can achieve satisfactory clinical and radiological outcomes after an acute first-time patellar dislocation.